Ldlr-/-.Leiden mice develop neurodegeneration, age-dependent astrogliosis and obesity-induced changes in microglia immunophenotype which are partly reversed by complement component 5 neutralizing antibody - Seidel, Florine; Fluiter, Kees; Kleemann, Robert; Worms, Nicole; van Nieuwkoop, Anita; Caspers, Martien P. M.; Grigoriadis, Nikolaos; Kiliaan, Amanda J.; Baas, Frank; Michailidou, Iliana; Morrison, Martine C. (Frontiers in Cellular Neuroscience, 2023)
Obesity has been linked to vascular dysfunction, cognitive impairment and neurodegenerative diseases. However, experimental models that recapitulate brain pathology in relation to obesity and vascular dysfunction are still lacking. In this study we performed the histological and histochemical characterization of brains from Ldlr-/-.Leiden mice, an established model for obesity and associated vascular disease. 18 week-old and 50 week-old Ldlr-/-.Leiden male mice were compared with age-matched C57BL/6J mice. We then assessed the effect of high-fat diet (HFD)-induced obesity on brain pathology in Ldlr-/-.Leiden mice and tested whether a treatment with an anti-complement component 5 antibody, a terminal complement pathway inhibitor recently shown to reduce vascular disease, can attenuate neurodegeneration and neuroinflammation. Histological analyses were complemented with Next Generation Sequencing (NGS) analyses of the hippocampus to unravel molecular pathways underlying brain histopathology. We show that Ldlr-/-.Leiden mice have more severe neurodegeneration and show an age-dependent astrogliosis that is not observed in age-matched C57BL/6J controls. This was substantiated by pathway enrichment analysis using the NGS data which showed that oxidative phosphorylation, EIF2 signaling and mitochondrial dysfunction pathways, all associated with neurodegeneration, were significantly altered in the hippocampus of Ldlr-/-.Leiden mice compared with controls. Obesity-inducing HFD-feeding did not aggravate neurodegeneration and astrogliosis. However, brains from HFD-fed Ldlr-/-.Leiden mice showed reduced IBA-1 immunoreactivity and increased CD68 immunoreactivity compared with chow-fed controls, indicating an altered overall microglial immunophenotype by HFD feeding. The systemic administration of an anti-C5 treatment partially restored the HFD effect on microglial immunophenotype. In addition, NGS data of hippocampi from Ldlr-/-.Leiden mice showed that HFD affected multiple molecular pathways: HFD notably inactivated synaptogenesis and activated neuroinflammation pathways. The anti-C5 treatment restored the HFD-induced effect on molecular pathways to a large extent. This study shows that the Ldlr-/-.Leiden mouse model is suitable to study brain histopathology and associated biological processes in a context of obesity and provides evidence of the potential therapeutic value of anti-complement therapy against obesity-induced neuroinflammation.